The Growth Of Body Length And Weigth Of Male Wistars Supplied With anchovies (stolephorus sp.) As additional diet - Indriana, Tecky (Insisiva Dental Journal, 2012)
Growth is affected by nutrition contents in the diet consumed.Nutrition playing role in the growth process is carbohydrate, protein, fat, mineral,water, and vitamins. Calcium is one of important minerals involving in cellmetabolism process needed in the process of growth and development. One ofsources of animal calcium is anchovy, besides its cheap price, anchovies may beconsumed wholy together with their bones. The purpose of this study was toobserve whether the supply of anchovies as additional diet may increase thegrowth of male wistars. Methods: A number of 12 male wistars divided into twogroups, control and experimental groups. The control group was only suppliedwith standard diet and sterile aquades, while the other group was supplied withanchovies as additional diet through oral sondage of 0,00062 gr/day x BW (BodyWeigth) for 40 days. Every wistar in each group was subsequently measured forits body length and weigth once a week to observe its growth and development.The data obtained were analized using anova test and LSD orderly. Results: Theresult demostrated the increase in the body length and weigth of the male wistarsof both groups in each week. Anova statistical test that was continued with LSDtest showed that there was significant increase (p<0,05) in the experimental groupin each week compared to the control group. Conclusion: The supply ofanchovies(Stolephorus sp) as additional diet may increase the growth of malewistars body length and weigth.